2008
DOI: 10.1590/s0102-05362008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de mudas de alface em função de substratos com e sem biofertilizante

Abstract: A alface é uma das hortaliças mais difundidas atualmente, sendo cultivada por todo o país. A sua larga adaptação às condições climáticas, a possibilidade de cultivos sucessivos no mesmo ano, o baixo custo de produção, a pouca suscetibilidade a pragas e a doenças e a comercialização segura, faz com que a alface seja a hortaliça preferida pelos pequenos produtores, o que lhe confere grande importância econômica e social, sendo significativo fator de agregação do homem do campo (Lima, 2005).A agricultura orgânica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
0
10
0
19
Order By: Relevance
“…The effectiveness of organic matter on the development of aerial biomass was demonstrated by Medeiros et al (2007) with cultivated rocket seedlings. In their study, the organic substrate yielded more leaves, demonstrating the ability of organic matter to increase photosynthesis activity in developing seedlings and improve performance and vigor after transplanting.…”
Section: Number Of Leavesmentioning
confidence: 99%
See 4 more Smart Citations
“…The effectiveness of organic matter on the development of aerial biomass was demonstrated by Medeiros et al (2007) with cultivated rocket seedlings. In their study, the organic substrate yielded more leaves, demonstrating the ability of organic matter to increase photosynthesis activity in developing seedlings and improve performance and vigor after transplanting.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Almeida et al (2011) found that substrates of cattle manure could be used to effectively increase the dry mass of shoots of passion fruit seedling. For the fresh and dry phytomass of rocket culture, The way in which a substrate affects the formation of the shoot is extremely important in seedling production because good shoot formation is essential for the development of plants and the volume of substrate in which roots can grow is limited in seedling tray production (OLIVEIRA et al, 2008). The shoot phytomass results also show that biochar cannot effectively replace cattle manure, at least the dosage of 40% cattle manure.…”
Section: Phytomassmentioning
confidence: 99%
See 3 more Smart Citations